The development of Parent-Implemented Social Communication Strategies in Autism (PICA) model using DDR approach - Ab Aziz, Analiza Anis; Mohamed Zain, Nor Azrita; Jusoh, Masnira; Zakaria, Rozanizam (Zes Rokman Resources, 2025)
The Parent-Implemented Social Communication Strategies in Autism (PICA) Model will be developed with the aim to address significant gaps in the intervention practices for children with Autism Spectrum Disorder (ASD). Using the Design and Development Research (DDR) approach, this study proposes a comprehensive and structured framework for developing, refining, and evaluating an intervention model that empowers parents as primary facilitators in improving their children's social communication skills. The PICA Model integrates iterative design processes, ensuring relevance in diverse cultural settings, particularly in Malaysia. The model incorporates evidence-based strategies, professional expertise, and parent feedback to create a practical solution for enhancing social communication outcomes. Despite the proven efficacy of parent-implemented interventions (PIIs), challenges such as accessibility, cultural relevance, and methodological rigour persist, hindering widespread implementation. The DDR approach addresses these issues by systematically refining the PICA Model, incorporating stakeholder input, and ensuring the model's adaptability across various family dynamics. This study focuses on three primary objectives: identifying the need for such a model, designing its components based on expert consensus, and evaluating its usability through expert feedback. The expected outcomes of this research include improved knowledge and skills for parents, better social communication outcomes for children, and the potential for widespread adoption among speech-language therapists (SLTs) in early intervention programs. The PICA Model significantly contributes to ASD intervention practices, aligning with the Sustainable Development Goals (SDGs) 3 and 4, promoting inclusive education and healthcare for children with special needs.